2016
DOI: 10.1063/1.4954982
|View full text |Cite
|
Sign up to set email alerts
|

Optimal spinneret layout in Von Koch curves of fractal theory based needleless electrospinning process

Abstract: Needleless electrospinning technology is considered as a better avenue to produce nanofibrous materials at large scale, and electric field intensity and its distribution play an important role in controlling nanofiber diameter and quality of the nanofibrous web during electrospinning. In the current study, a novel needleless electrospinning method was proposed based on Von Koch curves of Fractal configuration, simulation and analysis on electric field intensity and distribution in the new electrospinning proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The inner diameter of the spinnerets was 69 mm, the outer diameter was 79 nm and the thickness was 2 mm. More details about the device can be found in our previous work [22]. PI electrospinning solution (30% by wt.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inner diameter of the spinnerets was 69 mm, the outer diameter was 79 nm and the thickness was 2 mm. More details about the device can be found in our previous work [22]. PI electrospinning solution (30% by wt.)…”
Section: Methodsmentioning
confidence: 99%
“…We previously designed a needleless electrospinning device based on Von Koch fractal curves, which demonstrated better field intensity and distribution, and high productivity compared to multineedle electrospinning after simulation and analysis on the electric field. Further simulation and analysis by finite-element analysis software showed that the circular type of fractal spinneret with the second-level fractal structure exhibited better field intensity and distribution compared to other nonlinear fractal electrospinning technology (Figure 1) [22]. The present study takes advantage of the original needleless electrospinning device and employs it for the fabrication of composite nanofiber membranes for a lithium-ion separator.…”
Section: Introductionmentioning
confidence: 94%
“…Liu et al [22] first found the lightning-like jets in the bubble electrospinning. The fractal theory was successfully applied to controlling the shape of 2-D materials [23], and to designing optimally the spinneret [24], and now the fractal theory has become a useful mathematical tool to complex phenomena [25,26]. Traditional electrostatic spinning device schematic diagram was shown in fig.…”
Section: Electrospinning and Analysismentioning
confidence: 99%
“…They suggested that the spinneret with a larger curvature could form a higher electric field on a coil surface, which resulted in large nanofiber productivity and fine nanofibers with narrow diameter distribution. 12,16 Several researchers have reported on the increase in spinneret curvature by introducing an auxiliary structure onto needleless spinnerets, such as the Von Koch curve fractal structure, 17 needles on disk or helix slice, 18,19 barbed roller, 20 probed cylinder, 21 and threaded rod. 22 However, an uneven increase in local curvature can adversely lead to corona discharge and breakdown of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported on the increase in spinneret curvature by introducing an auxiliary structure onto needleless spinnerets, such as the Von Koch curve fractal structure, needles on disk or helix slice, , barbed roller, probed cylinder, and threaded rod . However, an uneven increase in local curvature can adversely lead to corona discharge and breakdown of the electric field. , Corona discharge not only increases the consumption of electrical energy, but also reduces the electrospinning efficiency and nanofiber production rate .…”
Section: Introductionmentioning
confidence: 99%